Social Capital as a Strengthener of Local Wisdom Identity of Fishermen Communities Muara Badak Ulu Village, Muara Badak Sub-district, Kutai Kartanegara Regency - Trisna Waty Riza Eryani; Muhammad Habibi; Putri Regina; William Christian (Manunggal Halim Jaya, 2024)
This study aims to explore and explain the strengths of social capital elements as reinforcers of local wisdom identity among the fishing community in Muara Badak Ulu Village, Muara Badak District, Kutai Kartanegara Regency. Fishermen, particularly traditional ones, face high risks at sea, with no guarantee of a catch to support their socio-economic needs. The local wisdom, deeply rooted in the fishing culture, is a key component of the social capital within this community. Social capital functions to enhance societal efficiency by facilitating coordinated actions through trust, norms, and networks. This research adopts a qualitative exploratory method, focusing on the core concepts of social capital: trust, norms, and networks. Data analysis is conducted using the interactive model of Miles, Huberman, and Saldana (2014), which involves data collection, data display, and drawing and verifying conclusions. The findings reveal that social capital is crucial in strengthening the local wisdom identity of the fishing community in Muara Badak Ulu. Trust among fishermen is vital, especially when at sea, and extends to local institutions, which provide necessary support such as funding, safety equipment, and boat engines, thereby forming networks. These networks, in turn, help preserve local wisdom traditions. Social norms also play a significant role by imposing social sanctions that prevent deviant behavior within the fishing groups and the broader community, thus reinforcing values like family, cooperation, and mutual aid.